1998
DOI: 10.1590/s0100-879x1998000400001
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated fats and immune function

Abstract: Animal studies suggest that olive oil is capable of modulating functions of cells of the immune system in a manner similar to, albeit weaker than, fish oils. There is some evidence that the effects of olive oil on immune function in animal studies are due to oleic acid rather than to trace elements or antioxidants. Importantly, several studies have demonstrated effects of oleic acid-containing diets on in vivo immune responses. In contrast, consumption of a monounsaturated fatty acid (MUFA)-rich diet by humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
(48 reference statements)
1
22
0
1
Order By: Relevance
“…These changes can affect the activity of transmembrane proteins, such as cell receptors and ionic channels (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These changes can affect the activity of transmembrane proteins, such as cell receptors and ionic channels (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium release -Fatty acids, particularly polyunsaturated acids, increase intracellular calcium concentrations, allowing a series of proteins to be modulated (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown the influence of dietary fat on fatty acid (FA) composition and oxidative stress in various tissues (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%